PROPRIEDADES VIBRACIONAIS E DIELÉTRICAS DA MULITA Bi2Mn4O10 - Silva Júnior, Flávio Moura e (2010)
In this work we investigated the vibrational properties of ceramics Bi2Mn4O10 (BMO) at room temperature by the Raman and Infrared spectroscopies, the phonons were classified by FG matrix method of Wilson. The dielectric properties of the material, in turn, were studied using the impedance spectroscopy in a range of 22 ° C to 275 ° C. Furthermore, static atomistic simulations were performed at BMO in the range 0.0 to 10 GPa with a step of 0.5 GPa. Concerning the Raman modes, ten out forty eight modes predicted by the group theory, were observed in our experimental spectrum while the spectrum of the imaginary part of inverse dielectric constant, we observe 19 LO modes active in infrared. By using the method of FG Wilson saw that the modes in the range of 600-760 cm-1 are stretching into the ab plane to the octahedral chains MnO6. Libration and bending modes were predicted to 400-570 cm-1 and 300-400 cm-1, respectively. It was further observed that the low-frequency modes are mainly due to translations of the Bi ions. The analysis of the impedance spectroscopy measurements led to the conclusion that the relaxing process of BMO are associated with conductive mechanisms, these being due to movement of polarons. The frequencies, for which the imaginary parts of the module (M '' ) and impedance ( Z '' ) exhibit a maximum, obeyed the Arrhenius law in its dependence on the reciprocal temperature, and the calculated activation energies were 0.57 eV and 0.63 eV for each case, respectively. The frequency dependent peaks that appeared in the Bode plot of the real part of dielectric constant were attributed to thermal relaxation processes associated with activated jumps of polarons. The simulations showed that the compound is quite stable, showing no structural phase transition in the pressure range investigated